2014
DOI: 10.1016/j.jnoncrysol.2014.03.016
|View full text |Cite
|
Sign up to set email alerts
|

High-performance thermoplastic composites poly(ether ketone ketone)/silver nanowires: Morphological, mechanical and electrical properties

Abstract: High-performance conductive thermoplastic composites poly(ether ketone ketone) (PEKK)/silver nanowires were elaborated by melt blending. Silver nanowires (AgNWs) with high aspect ratio (ξ~220) were elaborated through the polyol process in presence of poly(vinyl pyrrolidone) (PVP) and ethylene glycol. Scanning electron microscopy observations of nanowires were performed after an adapted cleaning process. The dispersion of NWs in the polymeric matrix was evaluated. A very low percolation threshold of 0.6 vol% wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 40 publications
10
65
3
Order By: Relevance
“…6 (a). This behavior is consistent with the study of Lonjon et al, where transition temperatures for PEEK were found to be unaffected with the addition of Ag NWs [12]. Crystallinity percentage of neat PLA and nanocomposites are provided in Fig.…”
Section: Thermal Propertiessupporting
confidence: 91%
See 3 more Smart Citations
“…6 (a). This behavior is consistent with the study of Lonjon et al, where transition temperatures for PEEK were found to be unaffected with the addition of Ag NWs [12]. Crystallinity percentage of neat PLA and nanocomposites are provided in Fig.…”
Section: Thermal Propertiessupporting
confidence: 91%
“…In addition, presence of aggregates also increases the t value. When we extrapolate the power law equation, conductivity of a nanocomposite filled with 100% fillers is calculated as 10 6.74±0.27 S/m, which is lower than the conductivity of bulk silver yet it is consistent with the Ag NW/polymer matrix conductive composites in literature [12].…”
Section: Electrical Conductivitysupporting
confidence: 75%
See 2 more Smart Citations
“…AgSWs are elaborated with a modified polyol process inspired by Sun and Wiley works . It consists in the reduction of AgNO 3 with ethylene glycol solution.…”
Section: Methodsmentioning
confidence: 99%